2009
DOI: 10.1007/s11030-009-9162-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in vitro antitubercular activity and 3D-QSAR study of 1,4-dihydropyridines

Abstract: In continuation of our research program on new antitubercular agents, this article is a report of the synthesis of 97 various symmetrical, unsymmetrical, and N-substituted 1,4-dihydropyridines. The synthesized molecules were tested for their activity against M. tuberculosis H (37)Rv strain with rifampin as the standard drug. The percentage inhibition was found in the range 3-93%. In an effort to understand the relationship between structure and activity, 3D-QSAR studies were also carried out on a subset that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…10 It is reported that 1,2,3-thiadiazole has beneficial medicinal and agricultural applications. Due to its good bioactivity and usefulness as intermediates in organic synthesis, the chemistry of the 1,2,3-thiadiazole ring has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…10 It is reported that 1,2,3-thiadiazole has beneficial medicinal and agricultural applications. Due to its good bioactivity and usefulness as intermediates in organic synthesis, the chemistry of the 1,2,3-thiadiazole ring has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a series of symmetrical and asymmetrical 1,4-DHPs was prepared, bearing a carbamoyl moiety at positions C-3 and C-5 or an aryl ring linked at the N-1 position of the 1,4-DHP scaffold (19). For these compounds the biological activity was evaluated and a 3D-QSAR analysis was carried out [75]. Recently, other imidazolyl-1,4-DHPs (20 and 21) have been reported to have certain antitubercular activity [76,77].…”
mentioning
confidence: 99%
“…[12] antitubercular agents. [13] Dihydropyridine derivatives have gained therapeutic success due to their efficient binding to the active site of the receptors.…”
Section: Introductionmentioning
confidence: 99%